Criteria for Diagnosis and Choice of Initial Antibiotic Therapy of Community-Acquired Pneumonia in Children According to Current Standards - Yu.K. Bolbot (Zaslavsky O.Yu., 2016)
The paper discusses the main criteria for the diagnosis of community-acquired pneumonia in children, the nature of the initial antibiotic therapy and the choice of optimal drugs.